Journal of Prosthodontics on Dental Implants 2015
DOI: 10.1002/9781119115397.ch27
|View full text |Cite
|
Sign up to set email alerts
|

Updated Clinical Considerations for Dental Implant Therapy in Irradiated Head and Neck Cancer Patients

Abstract: The article is associated with the American College of Prosthodontists' journal-based continuing education program. It is accompanied by an online continuing education activity worth 1 credit. Please visit www.wileyonlinelearning.com/jopr to complete the activity and earn credit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Several authors have proposed guidelines for prosthodontic rehabilitation of HNC patients, based primarily on the cumulative dose received at the implantation site . There is currently no consensus regarding the ideal timing of implant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have proposed guidelines for prosthodontic rehabilitation of HNC patients, based primarily on the cumulative dose received at the implantation site . There is currently no consensus regarding the ideal timing of implant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The use of orofacial and intraoral implants in prosthetic reconstruction has increased significantly in recent decades because of the development of restorative materials and surgical techniques. The implant‐supported prostheses seem to be a viable option, especially when the adverse effects of RT, such as xerostomia or friable mucosa, along with a compromised oral anatomy, hinder the use of conventional removable prostheses . Javed et al concluded that doses of radiation ≥50 Gy and ≤65 Gy did not result in any detrimental effects on the osseointegration of dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…Ihde et al concluded that doses >50 Gy decreased dental implant survival rates. Tanaka et al found that the placement of dental implants in the anterior mandible and a cumulative radiation dose that was <50 Gy resulted in a good survival rate for dental implants if the implants were inserted 12 months after RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased loss of marginal bone was reported by many authors, with 2-9 mm variations for a period of 3 years after implant surgery [16]. According to Tanaka [17], early failures are more frequent. In the studies, all failures occurred >1 year after implant placement.…”
Section: Discussionmentioning
confidence: 93%